Factors affecting consumer purchase intention: a survey of young adults on international cosmetic brands in Kuala Lumpur, Malaysia / Nur Liyana Bakarudin - Bakarudin, Nur Liyana (Faculty of Business and Management, 2015)
Nowadays, most of Malaysian young-adults are willing to spend a lot of money for the sake of taking care their appearance by buying trusted and high quality cosmetic products. Cosmetics which are available in Malaysian market are come from local products and international products. According to statistical data from Malaysia mission’s website, local cosmetics now are facing difficulties when competing with international cosmetics brands which aggressively entering Malaysian market. This research analyze the dominant factor that affect Malaysian young adults who live in the region of Kuala Lumpur to choose international cosmetics rather than local cosmetics, which are brand name, product quality, price, and packaging design. The objectives of the study conducted is to determine the dominant factor affecting consumer purchase intention between brand name, product quality, price, packaging design with purchase intention, and also to examine the contribution of brand name, product quality, price, and packaging design towards purchase intention. The totals of 150 respondents were selected from young-adults who are the users of international cosmetics at Shopping Complex in Kuala Lumpur. All data and information gathered through questionnaires were considered as primary data. The collected data are analyzed by using SPSS in order to identify the frequency analysis, cronbach’s alpha value, descriptive analysis, correlation analysis, and regression analysis. The result of this research is expected to be helpful for local cosmetics industries so they will improve and become the main preference for most Malaysian people.